Outcomes of physical therapy in patients with chronic low back pain: Učinki ambulantne fizikalne terapije pri bolnikih s kronično bolečino v križu - Klemenc Ketiš, Zalika (Acta Medico-Biotechnica, 2022)
Purpose: To assess the outcomes of a10–treatment sessions program of physical therapy regarding the level of pain and health–related quality of life in patients with chronic, non–specific, low back pain.Methods: A consecutive sample of adults (N = 129) with chronic, non–specific, low back pain was assessed for improvement after a 10–day physical therapy program, consisting of an average of 3 different physical modalities, as prescribed by family physicians. A visual analog pain scale and EuroQol questionnaire (EQ–5D and EQ–VAS) were completed by patients before and after physical therapy.Results: The intensity of pain after 10 days of physical therapy was on average lower (1.7 ± 1.8 points; P < 0.001). The assessment of overall health on the EQ–VAS was on average better (10.3 ± 15.2 points; P < 0.001). The score of the EQ–5D was on average lower (0.8 ± 1.2 points; P < 0.001). The patients that were not on sick leave during the physical therapy reported a greater lowering of the intensity of pain than those on sick leave (P = 0.03). Patients with a BMI > 29 kg/m2 had a significantly higher change in the assessment of overall health on the EQ–VAS (P = 0.022). The patients that had group exercise in the set of procedures reported a greater improvement in overall health on the EQ–VAS compared to the patients that didnot have group exercise (P = 0.036). The patients with anxiety and depression had a significantly higher change in the composite score of the EQ–5D (P = 0.013). Patients with a BMI > 29 kg/m2 had a significantly higher change in the composite score of the EQ–5D (P = 0.013).Conclusion: Physical therapy has some effect in the short–term treatment of patients with chronic, non–specific, low back pain, but the viability of such procedures in this population of patients is questionable.
Keywords: physical therapy modalities; out- comes assessment; low back pain